Chondroitinase ABC Promotes Axon Regeneration and Reduces Retrograde Apoptosis Signaling in Lamprey - Hu, Jianli; Rodemer, William; Zhang, Guixin; Jin, Li-Qing; Li, Shuxin; Selzer, Michael E. (Frontiers in Cell and Developmental Biology, 2021)
Paralysis following spinal cord injury (SCI) is due to failure of axonal regeneration. It is believed that axon growth is inhibited by the presence of several types of inhibitory molecules in central nervous system (CNS), including the chondroitin sulfate proteoglycans (CSPGs). Many studies have shown that digestion of CSPGs with chondroitinase ABC (ChABC) can enhance axon growth and functional recovery after SCI. However, due to the complexity of the mammalian CNS, it is still unclear whether this involves true regeneration or only collateral sprouting by uninjured axons, whether it affects the expression of CSPG receptors such as PTPσ, and whether it influences retrograde neuronal apoptosis after SCI. In the present study, we assessed the roles of CSPGs in the regeneration of spinal-projecting axons from brainstem neurons, and in the process of retrograde neuronal apoptosis. Using the fluorochrome-labelled inhibitor of caspase activity (FLICA) method, apoptotic signalling was seen primarily in those large, individually identified reticulospinal (RS) neurons that are known to be “bad-regenerators”. Compared to uninjured controls, the number of all RS neurons showing polycaspase activity increased significantly at 2, 4 and 8 weeks post-transection (post-TX). ChABC application to a fresh TX site reduced the number of polycaspase-positive RS neurons at 2 weeks and 11 weeks post-TX, and also reduced the number of active caspase 3-positive RS neurons at 4 weeks post-TX, which confirmed the beneficial role of ChABC treatment in retrograde apoptotic signaling. ChABC treatment also greatly promoted axonal regeneration at 10 weeks post-TX. Correspondingly, PTPσ mRNA expression was reduced in the perikaryon. Previously, PTPσ mRNA expression was shown to correlate with neuronal apoptotic signalling at 2 and 10 weeks post-TX. In the present study, this correlation persisted after ChABC treatment, which suggests that PTPσ may be involved more generally in signalling axotomy-induced retrograde neuronal apoptosis. Moreover, ChABC treatment caused Akt activation (pAkt-308) to be greatly enhanced in brain and spinal cord post-TX, which was further confirmed in individually identified RS neurons. Thus, CSPG digestion not only enhances axon regeneration after SCI, but also inhibits retrograde RS neuronal apoptosis signalling, possibly by reducing PTPσ expression and enhancing Akt activation.